MENINGKATKAN HASIL BELAJAR PPKN DENGAN MENGGUNAKAN METODE PEMBERIAN TUGAS SISWA KELAS V SDN 012 SILIKUAN HULU - ', Waldiyem (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low student learning outcomes Civics class V SDN 012Silikuan Hulu. This research is a class act, done in class V SDN 012 Silikuan Hulu. This studywas conducted by two cycles, the data used in the study to focus on improving studentlearning outcomes Civics. The study states that PPKn learning outcomes of students hasincreased, it is in conformity with the results of the research on preliminary data the averagevalue of 60 students, the first cycle increased to 65 and the second cycle increased again to70. In addition, the number of students who completed the cycle I was 6 students, pad firstcycle increased with the number of students 9 students and the second cycle increased againto 12 students. Based on this it can be concluded that the application of the method ofadministration tasks can improve the learning outcomes of students of class V PPKn SDN 012Silikuan Hulu.